From Colonialism to Imperialism: The Journey Motif in Mongo Beti’s Remember Ruben - Mohammed Sani, Abubakar; L. Ashituabe, Justina; Lawal, Sule (IJRDO - Journal of Social Science and Humanities Research, 2016)
The situation and the living condition of both the people and the Africa continent are deteriorating by day even after many years of the so much desired political self-independence from the colonizers. Despite the abundant human and natural resources endowed in the continent, the political leaders hitherto depend on aids and grants from the Western powers for the survival of the different independent African countries. The continent and its peoples are ranked among the poorest in the world. However, this study argues that the main cause of this unfortunate situation is as a result of the continued existence of colonialism but in a different form known as imperialism. This started from the kind of independence granted to the African countries by the colonial masters, where they ensured that they planted stooges and puppets as leaders in almost all African countries during the independence. This trend is still on-course in almost all the so-called independent African countries. Certainly, there was resistance by the nationalists in some countries against this agenda by the West but the groups were crushed by the military might of the colonizers. Thus, the journey started by colonizers is still on course in Africa but in the form imperialism (Journey motif). It is this kind of situation that Mongo Beti depicted in his novel Remember Ruben, highlighting on the struggle made by the nationalists during independence in Cameroon to resist the imposition of puppet that will be indirectly controlled by the colonizers. Beti believes that with an imperial puppet on the helms the independence of Cameroon particular and Africa as a whole will forever remain a mere chimera.